PENERAPAN RCM PADA SISTEM DISTRIBUSI AIR DI PDAM PASIR PUTIH PEMATANGAN BARANGAN KABUPATEN ROKAN HULU - Legisnal Hakim; Fahrizal - (Jurnal APTEK, 2012)
Rokan Hulu regency government is very concerned with people's needs for clean water for the most budget Rokan Hulu regency government owned companies to build infrastructure through water distribution unit called the Badan Pengelolaan Air Bersih (BPAB), one unit of water distribution net is BPAB Pematang Barangan-Pasir Putih. A water distribution unit is a group function, system, sub system, and item components are complete and mutual support for the smooth operation and water distribution.In water distribution unit BPAB Pematang Barangan for water distribution system using a centrifugal pump, with sub pump system with a single puff volut brands Ebara PUMP. To reduce the downtime of time it needs to be done to improve the availability of treatment / usability (availability) in the system function. In order to serve the function of the system can then use Reliability Centered Maitenance(RCM) method to be implemented by means of qualitative analysis on the component item that can be analyzed in detail the use of Failure Mode Effect Analisys (FMEA), Logic Tree ANALISYS, and Maintenance Task.